Cultural policy in crisis contexts: the crossroads of the National Culture Policy - Lossio Chávez, Félix Antonio (2023)
This article has as its central argument that cultural policy and management in Peru occurs in a context of disjointed dynamics and precarious consolidation, which destabilizes, but at the same time requires, an articulating narrative of its guiding framework, the National Cultural Policy 2030. In particular, it is argued that the scenario that defines current cultural policy and management in Peru is characterized, on the one hand, by notable advances from both civil society and the public and private sector in different aspects of the cultural field, as well as as well as the affirmation of consensus in relation to new approaches for the development of the cultural sector. But also, and simultaneously, characterized by an institutional-administrative uncertainty, the multiple crises and the absence of political horizons in relation to the field of culture. This results in a National Cultural Policy 2030 (PNC 2030) that is based on necessary premises and approaches in tune with the global cultural agenda, which is based on solid evidence and that outlines necessary objectives for strengthening the sector in the country; but which is uncertain regarding its sustainability, results and social legitimacy. Therefore, this article suggests that the main challenge of the PNC 2030 —and cultural management in Peru— is to act in a scenario without guarantees and, from there, recover its ethical-political dimension using the tools of public administration.